Directive Speech Act used by Isabel Conklin in The Summer I Turned Pretty Novel - Dahlan, Nurasisah; Maca, Sudirman; Wahyuni, Rezki Amalia (Fakultas Sastra, Universitas Bosowa, 2024)
This study investigates the use of directive speech acts by Isabel Conklin in Jenny Han's novel,